Using training aids. Memaksimalkan potensi alat bantu dalam pendidikan dan latihan - RAE, Leslie (BHUANA ILMU POPULER, 2005)
Using training aids. Memaksimalkan potensi alat bantu dalam pendidikan dan latihan